Becoming Creole : nature and race in Belize - Johnson, Melissa A., 1962- (New Brunswick, New Jersey : Rutgers University Press, 2019)
Becoming Creole explores how people become who they are through their relationships with the natural world, and it shows how those relationships are also always embedded in processes of racialization that create blackness, brownness, and whiteness. Taking the reader into the lived experience of Afro-Caribbean people who call the watery lowlands of Belize home, Melissa A. Johnson traces Belizean Creole peoples' relationships with the plants, animals, water, and soils around them, and analyzes how these relationships intersect with transnational racial assemblages. She provides a sustained analysis of how processes of racialization are always present in the entanglements between people and the non-human worlds in which they live. -- Provided by publisher
Introduction: becoming Creole -- Hewers of wood : histories of nature, race and becoming -- Bush: racing the more than human -- Living in a powerful world -- Entangling the more than human : becoming Creole -- Wildlife conservation, nature tourism and Creole becomings -- Transnational becomings : from deer sausage to tilapia -- Conclusion: livity and (human) being -- Appendix: Kriol words and phrases used in text.
Includes bibliographical references and index.
Print version record.
In English.
eBooks on EBSCOhost
Keywords: Ethnology -- Belize; Multiracial people -- Belize; Ethnologie -- Belize; SOCIAL SCIENCE -- General; Ethnology; Multiracial people; Belize; Natur; Identität; Belize